Abnormal sensory integration affects balance control in hemiparetic patients within the first year after stroke - Oliveira, Clarissa B. (2011)
OBJECTIVE: Impairments in balance can be a consequence of changes in the motor, sensory, and integrative aspects of motor control. Abnormal sensory reweighting, i.e., the ability to select the most appropriate sensory information to achieve postural stability, may contribute to balance impairment. The Sensory Organization Test is a component of Computerized Dynamic Posturography that evaluates the impact of visual, vestibular, and somatosensory inputs, as well as sensory reweighting, under conditions of sensory conflict. The aim of this study is to compare balance control in hemiparetic patients during the first year post-stroke and in age-matched neurologically normal subjects using the Berg Balance Scale and Computerized Dynamic Posturography. METHODS: We compared the Berg Balance Scale and Sensory Organization Test scores in 21 patients with hemiparesis after first-ever ischemic stroke and in 21 age-matched, neurologically normal subjects. An equilibrium score was defined for each Sensory Organization Test condition. RESULTS: Berg Balance Scale scores were significantly lower in the patients than in the neurologically normal subjects. Equilibrium scores were significantly lower in the patients than in the neurologically normal subjects for those Sensory Organization Test conditions that did not provide appropriate somatosensory information and under conditions of sensory conflict. A history of falls was more frequent in patients with lower equilibrium scores. CONCLUSION: During the first year after a stroke, defective sensory reweighting significantly impacts balance control in hemiparetic patients. These results are important for the planning of effective rehabilitation interventions.